MODEL ERP DAN MANAJEMEN RANTAI PASOK UNTUK KOPERASI; KAJIAN PUSTAKA - Yunani, Akhmad (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2019)
ERP system and SCM are considered to be the business performance enhancer regardless the business type. This paper summarizes studies on ERP systems and SCM in cooperative business. The cooperative is a unique model of business, where the owners are also customers, suppliers, as well as operators. There is a little study concerns on ERP, SCM, even operations perspective of cooperative business. If any, the study focuses on technical aspects of technology, a little part of ERP, like the use of application of accouting, the use of marketplace, etc. This paper also proposes a framework of ERP and SCM model for cooperative. The discussion refers to the performance standards of the cooperative set by the Government and combined with ERP systems and business process in general. This model is expected to be a considerable framework to enhance cooperative performance as well as a tool of control of cooperative business. Due to the vary of cooperative type of business, it is suggested that further study observes the actual business process in a cooperative so that ERP system and SCM model can be developed properly.